Estudo do coeficiente de distribuição transversal de cargas móveis em pontes de vigas mistas de aço e concreto - Castro, Thiago da Silva (2016)
This study aims to develop a study to evaluate the behavior transverse distribution of loads generated by the passage of vehicles for brazilian standards and brazilian construction characteristics, using finite element analysis. The American standards (AASHTO-LRFD) and European (EUROCODE), describe equations and transverse distribution models for bridges with the constructive characteristics and own vehicles in their countries. In Brazil the current regulations on the subject are based on data adapted these standards. The development of this study was based on creating structural models of composite beams of steel and concrete bridges, using finite element methods, lines of influence and AASHTO standard, to afford the transverse distribution coefficients for the features of vehicles and buildings brazilian. The methodology used to obtain the factors, It was based on the development of finite element models with variation in the characteristics of bridges ranging: length, number of beams and bems sections. 120 analyzes were generated for each of the proposed methods, with the purpose to develop equations that can relate the distribution phenomenon of actions that occur on the board and how they are distributed to the beams, thus numerically exhibit this behavior. To obtain the results it was possible to formulate equations describing the behavior of structures for the purpose of bending and shear, with limitations for use in structures with linear beams and within the limits studied.